PASSIVE LIGHTING DISTRIBUTION SYSTEM IN EDUCATIONAL BUILDINGS CASE STUDY OF PPIG BUILDING, PALANGKARAYA UNIVERSITY - Onie D. Sanitha; Theo Fransisco; Novera Kristianti; Yunida Iashania; Taufiqurahman; Audy Mirelia W.S; Yusuf Aditya Sihombing (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
This study explores the passive lighting distribution system in educational buildings at PPIG Palangka Raya University. The main focus of the study is how the distribution of natural lighting decreases significantly in spaces that are far from the lighting source, especially in buildings that have light sources on the side that is difficult to reach the entire space. Using an analysis test with the Andrewmarsh application, the distribution of lighting in the Daylight Factor was found with an average of 43.48%. The results of the study show that the placement of space towards the position of windows or openings that are less strategic causes a gap in light distribution, thus affecting visual comfort in the room. This study is expected to be a reference in designing educational buildings that are more energy efficient and comfortable for their users.